Investigation of fracture process zone development in quasi-isotropic carbon/epoxy laminates using in situ and ex situ X-ray Computed Tomography. (March 2023) - Xu, Xiaodong; Takeda, Shin-ichi; Wisnom, Michael R.
Abstract: Trans-laminar fracture toughness is an important property of laminated composites and examining the fracture process zone at the tip of a crack is key to understanding it. To date, little research has been done on in-depth examination of the early fracture process zone development in quasi-isotropic laminates. In this work, detailed in situ X-ray Computed Tomography (CT) analyses enabled continuous examination under loading and better understanding of the entire fracture process zone development. Ex situ CT scanning of an additional hot temperature wet conditioned specimen with dye penetrant was also employed as a comparison to explain the significance of 0° splitting to trans -laminar fracture.